The protest box - Badger, Gerry; Parr, Martin, 1952- (Göttingen : Steidl ; London : Thames & Hudson [distributor], 2010)
Martin Parr's The protest box is a box set which brings together five photobooks as facsimile reprints. Parr has selected diverse books which each deal with the subject of protest in quite different ways. From the documentation of various protest movements to the actual book being a form of protest, all these reprints are gems within the history of photographic publishing. The box set is accompanied by a booklet which includes an introduction by Martin Parr, an essay discussing the wider context of these books by Gerry Badger, and English translations of all the texts in the books.
- The protest box / Martin Parr ##- América: un viaje a través de la injustica / Enrique Bostelmann ##- Para verte mejor, América Latina / Paolo Gasparini, Edmundo Desnoes ##- Algerien L' Algérie / Dirk Alvermann ##- Sanrizuka / Kitai Kazuo ##- Immagini del no / Paolo Mattioli and Anna Candiani.
Enkel te raadplegen op aanvraag
Texts in Spanish, Italian, German and Japanese, with English translations.
6 books wrapped in 1 sheet of black paper. Limited edition of 1,000 copies.
In slip case.
boek